If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -7) = 0 Reorder the terms: (-7 + 4x) = 0 Remove parenthesis around (-7 + 4x) -7 + 4x = 0 Solving -7 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 4x = 0 + 7 4x = 0 + 7 Combine like terms: 0 + 7 = 7 4x = 7 Divide each side by '4'. x = 1.75 Simplifying x = 1.75
| (x^2)-6(x)-1=0 | | 9w^6+42w^5+24w^4= | | 24x-36x^2=0 | | 8(6x-7)=96x | | -1/4(12x+4)+1/7(49x+21) | | 8-7x=119-28x | | 2x+3=x+85 | | -x^2+17x-23=5x+9 | | x^4-4x^2-2=0 | | 1.16y=y+1+0.5 | | 50-7x=20x+20 | | 5x+4=28x+12 | | 1.16y=y+1+0.3 | | 1.2=2x/3+5.1 | | 1.16y=y+1+1 | | x/5+8=6 | | -x^2+2x+58=-x+4 | | x/5+12=-20 | | 5x/2=11+2x/3 | | 3x^2y-6xy^2= | | 6x+13=69-3x | | 1/3(5-3x)=5/6(x-2) | | x-39=79 | | 6(3x-12)=54x | | 13x+12=5x+10 | | 5m+20=6m+12 | | -3(x-2.7)=1.8 | | 5y^2-17y+14= | | -5x^2-5x+10=-2x^2-4x+7 | | 7(x-3)=-4x+89 | | 8.4=-6(a+2.4) | | -3x^2-11x+5=-4x+6 |